2007
DOI: 10.1016/j.engfracmech.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Statistical failure analysis of adhesive resin cement bonded dental ceramics

Abstract: The goal of this work is to quantitatively examine the effect of adhesive resin cement on the probability of crack initiation from the internal surface of ceramic dental restorations. The possible crack bridging mechanism and residual stress effect of the resin cement on the ceramic surface are examined. Based on the fracture-mechanics-based failure probability model, we predict the failure probability of glass-ceramic disks bonded to simulated dentin subjected to indentation loads. The theoretical predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In addition, Rosenstiel et al have found that resin cement can significantly increase the flexural strength of a glass ceramic when compared to glass ionomer cements [19]. In this study, the flexural strength of etched ceramic increased significantly after the application of resin cement, even for acid etching time as short as 20 s. Investigators suggested that the use of silane and a layer of resin luting agent can increase the strength of glass ceramic due to crack bridging [20,21]. At the molecular level, surface cracks are manifested as gaps in the arrangement of the ions.…”
Section: Fig 2 -Sem Images Of Ceramic/cement Interface When the Sampmentioning
confidence: 54%
“…In addition, Rosenstiel et al have found that resin cement can significantly increase the flexural strength of a glass ceramic when compared to glass ionomer cements [19]. In this study, the flexural strength of etched ceramic increased significantly after the application of resin cement, even for acid etching time as short as 20 s. Investigators suggested that the use of silane and a layer of resin luting agent can increase the strength of glass ceramic due to crack bridging [20,21]. At the molecular level, surface cracks are manifested as gaps in the arrangement of the ions.…”
Section: Fig 2 -Sem Images Of Ceramic/cement Interface When the Sampmentioning
confidence: 54%
“…Experimentally determined surface flaw size distribution and FE stress calculations are combined on the basis of fracture mechanics based statistical failure probability model to predict failure probability distribution. The theoretical predictions are verified against experimental failure probability data based on single-cycle indentation tests on flat samples [24,25] . Using experimentally determined ceramic fatigue data, this method is extended to predict lifetime under cyclic loadings [12] .…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, to further improve the standardization of the study set-up resin composite root dies were fabricated in series using a resin composite with a standardized silicon mold instead of prepared natural teeth. A resin composite with an elastic modulus (22 GPa) similar to that of the dentinal tissue was employed as substitute for dentin [9,11,18,19].…”
Section: Discussionmentioning
confidence: 99%